Computationally assessing diamond as an ultrafast pulse shaper for high-power ultrawideband radar - Herrmann, Christopher S.; Croman, Joseph; Baryshev, Sergey V. (Frontiers in Carbon, 2023)
Diamond holds promise to reshape ultrafast and high power electronics. One such solid-state device is the diode avalanche shaper (DAS), which functions as an ultrafast closing switch where closing is caused by the formation of the streamer traversing the diode much faster than 10 7 cm/s. One of the most prominent applications of DAS is in ultrawide band (UWB) radio/radar. Here we simulate a diamond-based DAS and compare the results to a silicon-based DAS. All DAS were simulated in mixed mode as ideal devices using the drift-diffusion model. The simulations show that diamond DAS promises to outperform Si DAS when sharpening kilovolt nanosecond input pulse. The breakdown field and streamer velocity (∼10 times larger in diamond as compared to those in Si) are likely to be the major reasons enabling kV sub-50 ps switching using diamond DAS.